2019
DOI: 10.1363/psrh.12118
|View full text |Cite
|
Sign up to set email alerts
|

Women's Expectation of Receiving Reproductive Health Care at Catholic and Non‐Catholic Hospitals

Abstract: CONTEXT : Catholic hospitals operate under directives that prohibit the provision of contraceptives, sterilization and abortion. Little research has examined women ' s awareness of these institutions' policies, which aff ects their ability to make informed decisions about where to seek care. METHODS :In 2016, some 1,430 women aged 18-45 were recruited from a U.S. probability-based research panel for a survey about hospital care. Respondents were randomized to a hypothetical Catholic or nonreligious hospital gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…This false documentation can lead to medical errors, and it forces providers to choose between professional integrity and patient care. Given the federal government's proposed policies to expand protections for conscientious objection, policymakers should prioritize efforts to protect the conscientious provision of reproductive care with as much vigor as they do conscientious refusals of care, to help clinicians avoid the ethically problematic practice of false documentation . Furthermore, these practices may stigmatize contraception and burden patients, especially underserved populations with social and financial constraints, thus delaying and negatively affecting patient care.…”
Section: Discussionmentioning
confidence: 99%
“…This false documentation can lead to medical errors, and it forces providers to choose between professional integrity and patient care. Given the federal government's proposed policies to expand protections for conscientious objection, policymakers should prioritize efforts to protect the conscientious provision of reproductive care with as much vigor as they do conscientious refusals of care, to help clinicians avoid the ethically problematic practice of false documentation . Furthermore, these practices may stigmatize contraception and burden patients, especially underserved populations with social and financial constraints, thus delaying and negatively affecting patient care.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Catholic hospitals do not adequately inform patients about restrictions on care, leaving many patients unaware of miscarriage management policies. 14,16,17 Moreover, Catholic hospitals are not required to disclose their religious affiliation or specific policies to patients, except in Washington state, which mandates that they provide their reproductive health and end-of-life care policies on their websites. 18 Policy restrictions and treatment options are often not disclosed even when a patient presents to a Catholic hospital during miscarriage.…”
Section: Anticipatory Counseling About Miscarriage Management In Cathmentioning
confidence: 99%
“…8,19 In a national survey of women aged 18-45 from 2018, Wascher and colleagues found that more than a third of women who named a Catholic hospital as their primary hospital for reproductive care were unaware of its Catholic affiliation, 20 and Stulberg et al reported that most women were unaware of how religious policies impacted reproductive care. 16 Notably, the population of women seeking care in Catholic hospitals is demographically comparable to women nationally in terms of religion and religiosity, and most individuals do not choose a hospital based on its religious affiliation. 20,21 Furthermore, women expect to receive comprehensive reproductive health care services from both Catholic and secular institutions.…”
Section: Anticipatory Counseling About Miscarriage Management In Cathmentioning
confidence: 99%
See 1 more Smart Citation
“…When surveyed about their expectations for reproductive care at a Catholic hospital, 69% of women expected that they could receive birth control from an obstetrician/gynecologist (OBGYN), 63% that sterilization would be available, 44% that in vitro fertilization would be available, and 27% that abortion would be an option if the fetus had a serious health condition. 10 The directives that doctors in Catholic facilities must follow prohibit provision of all of these services, but many women did not anticipate denials of care.…”
Section: Transparencymentioning
confidence: 99%